THE EFFECT OF POPULATION AND GRDP AND POVERTY ON ECONOMIC GROWTH IN MAKASSAR CITY - Sandira, Nur Fadilah Ayu (Journal of Business Issues, 2022)
This study aims to analyze the impact of Population, Gross Regional Domestic Product (GRDP), poverty, and economic growth in Makassar City. This research is quantitative research. The type of data used in this study is secondary data in the form of annual time series starting from 2009 to 2018 wich are quantitative data. Data analysis was done using multiple linier regression statistical analysis with path analysis type. The results of this study show that population and GRDP have no significant influence on poverty and population and GDRP has no significant influence on economic growth and poverty has a significant influence on economic growth in Makassar City.